The siege of Sziget - Zrínyi, Miklós, gróf, 1620-1664 (Book collections on Project MUSE., 2011)
"In 1566, Croatian Count Miklós Zrínyi defended the Fortress of Szigetvár against an overwhelming Ottoman siege for 33 days. In the end, with troops and supplies exhausted, he led the remainder of his men in a last charge into the enemy lines, killing thousands before being killed themselves. Almost a hundred years later in 1651, Zrínyi's great-grandson, also Miklós Zrínyi and himself a famed general, composed an epic poem of some 1,500 stanzas recalling in vivid and often fantastic detail the events of the siege, the heroes on both sides, and the climactic final sortie that led to defeat for the Hungarians and painfully empty victory for the Turks. The epic, written in the fashion of Homer and Tasso, does not content itself with just a historical retelling, however. Written when the Ottoman threat was again looming large over all of Europe, the poet sought to marshal his countrymen, and indeed all Christians, against the cause of the overwhelming forces from the East. He framed his story, therefore, in the larger context of God's burning anger against the apostasy of his followers, which he uses the Turkish invasion to punish. It is only with a return to piety that the Christians can restore God's favor, but if they do -- woe to their invaders! The hero, Zrínyi, is one such believer, who is as likely to give a moving speech on the righteousness and supremacy of God's will as he is to massacre those who would assault his home. God rewards him with a martyr's death, but not before giving him the glory of finishing off Sultan Suleiman himself, as the demons summoned by the Sultan's wizard battle the angels who have come to claim the defenders' souls. Part chronicle of war, part theological treatise, the poem also has episodes of romance and adventure, as each side is at once humanized and made larger than life. The work is today considered to be one of the cornerstones of Hungarian literature, and one of most important works of the seventeenth century of any language, but has been virtually unknown and entirely inaccessible outside of Hungary -- until now."--Publisher's description.